Why are fruits colorful? The relative importance of achromatic and chromatic contrasts for detection by birds - Cazetta, Eliana [UNESP]; Schaefer, Hinrich Martin; Galetti, Mauro [UNESP] (Springer, 2009)
The colors of fruits and flowers are traditionally viewed as an adaptation to increase the detectability of plant organs to animal vectors. The detectability of visual signals increases with increasing contrasts between target and background. Contrasts consist of a chromatic aspect (color) and an achromatic aspect (light intensity), which are perceived separately by animals. To evaluate the relative importance of fruits' chromatic and achromatic contrasts for the detection by avian fruit consumers we conducted an experiment with artificial fruits of four different colors in a tropical forest. We displayed the fruits against two different backgrounds, an artificial background and a natural one, because they differed in achromatic properties. We found no effect of the type of background on fruit detection rates. Detection rates differed for the four fruit colors. The probability of detection was explained by the chromatic contrast between fruits and their background, not by the achromatic contrasts. We suggest that birds attend primarily to chromatic contrast probably because these are more reliably detected under variable light conditions. Consistent with this hypothesis, we found habitat-specific differences in the conspicuousness of natural fruit colors in the study area. Fruits of understory species that are subjected to the variable light conditions within a forest displayed higher chromatic contrasts than species growing in the open restinga forest with constant bright illumination. There was no such difference for achromatic contrasts. In sum, we suggest that fruit colors differ between habitats because fruit colors that have strong chromatic contrasts against background can increase plants' reproductive success, particularly under variable light conditions.
Keywords: Atlantic forest; Eye model; Frugivory; Plant-animal interaction; Signal